CONSUMPTION EXPENDITURE PATTERN AND INEQUALITY AMONG AGRICULTURAL HOUSEHOLDS IN SOUTH COASTAL REGION OF ANDHRA PRADESH STATE - M. AREEF*, Y. RADHA, V.S. RAO, P.V.S. GOPAL, K.S.R. PAUL, K. SUSEELA and S. RAJESWARI (The Journal of Research ANGRAU, 2023)
The study is an attempt to analyse consumption pattern and inequality by distinguishing totalconsumption expenditure into food items and non-food items. Average propensity to consumption(APC) was formulated to know the proportion of income consumed. Engel ratio was estimated to knowthe difference in expenditure on each of food and non-food items separately by the agriculturalhouseholds. Lorenz curve, Gini index, Atkinson’s index and Theil index were employed to measurethe consumption expenditure inequality for agricultural households across landholding categories.The results of Gini, Atkinson and Theil indices showed that within the landholding category exceptsemi-medium farmers, the expenditure distribution was more unequal for non-food items than fooditems. The marginal farmer households reported with more unequal distribution of consumptionexpenditure (Gini=0.2221).